2011
DOI: 10.3390/molecules16108874
|View full text |Cite
|
Sign up to set email alerts
|

Autotoxicity and Allelopathy of 3,4-Dihydroxyacetophenone Isolated from Picea schrenkiana Needles

Abstract: Bioassay-guided fractionation of the diethyl ether fraction of a water extract of Picea schrenkiana needles led to the isolation of the phenolic compound 3,4-dihydroxy- acetophenone (DHAP). The allelopathic effects of DHAP were evaluated under laboratory conditions on P. schrenkiana, rice (Oryza sativa L.), wheat (Triticum aestivum L.), radish (Raphanus sativus L.), lettuce (Latuca sativa L.), cucumber (Cucumis sativus L.) and mung bean (Phaseolus radiatus L.). DHAP significantly inhibited seed germination and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 41 publications
2
29
0
Order By: Relevance
“…Schrenkiana , so it was hypothesized that 0.25 mM DHAP might be the inflection point of changing action direction. It was near to the concentration of 0.224 mM in natural forest conditions [32]. Thus, our investigation provided evidence on the phytotoxic potential of P .…”
Section: Discussionsupporting
confidence: 54%
“…Schrenkiana , so it was hypothesized that 0.25 mM DHAP might be the inflection point of changing action direction. It was near to the concentration of 0.224 mM in natural forest conditions [32]. Thus, our investigation provided evidence on the phytotoxic potential of P .…”
Section: Discussionsupporting
confidence: 54%
“…Compound 1 (7) (Machida & Kikuchi, 1993), p-hydroxyphenyl 6-O-cis-p-Coumaroyl-b-D-glucopyranoside (8) (Machida & Kikuchi, 1993), 4-hydroxybenzoic acid (9) (Rukachaisirikul et al 2010), 4-(methoxymethyl) phenyl-1-Ob-D-glucopyranoside (10) , 3,4-dihydroxyacetophenone (11) (Ruan et al 2011), 3,4-dihytroxy benzaldehyde (12) , p-hytroxy benzaldehyde (13) (Yang et al 2013 ), 3-O-(b-D-glucopyranosyl)-1-(3 0 5 0 -dimethoxy-4-hydroxyphenyl-1-propanone (21) , myzodendrone (22) (Desmarchelier et al 2005) were identified by comparisons with spectroscopic data of literatures.…”
Section: Resultsmentioning
confidence: 99%
“…In natural forest conditions, one gram of dry soil from a mature P. Schrenkiana forest was determined to contain 0.51 ± 0.03 mg DHAP (Ruan et al. 2011). If DHAP in 1 g field soil was dissolved into 15 mL snow or rain water, the concentration of DHAP would be 0.224 mmol/L which was near to the concentration of inflection point.…”
Section: Discussionmentioning
confidence: 99%
“…The phenolic compound 3,4‐dihydroxy‐acetophenone (DHAP) isolated by bioassay‐guided fractionation from the diethyl ether fraction was proved to be the major autotoxic chemical in P. Schrenkiana needles (Ruan et al. 2011). …”
Section: Introductionmentioning
confidence: 99%